2016
DOI: 10.1007/s10068-016-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of squid protein hydrolysates prepared with papain using response surface methodology

Abstract: Squid protein hydrolysates (SPH) were prepared from the Indian squid using papain. Response surface methodology (RSM) was used for optimization of hydrolysis conditions, including temperature, time, and the enzyme-substrate ratio using DPPH radical scavenging activity as a response. The amino acid composition of SPH was compared with raw squid muscle. antioxidant activities were evaluated based on reducing power, metal chelation, ABTS, hydroxyl radical, and superoxide anion radical scavenging assays. SPH exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…In the linoleic acid model system, the tripeptide (WPP) isolated from the clam protein hydrolysate showed lipid peroxidation reduction ability similar to GSH [246]. In the sardine minced meat model system, the squid protein hydrolysate prepared by Papain has similar lipid oxidation inhibition ability as ascorbic acid [247]. Zein hydrolysate has been proven to effectively inhibit lipid oxidation, reduce the production of hydrogen peroxide and TBARS, and significantly improve the oxidative stability of model oils [248].…”
Section: Functional Ingredients To Stabilize Food Qualitymentioning
confidence: 99%
“…In the linoleic acid model system, the tripeptide (WPP) isolated from the clam protein hydrolysate showed lipid peroxidation reduction ability similar to GSH [246]. In the sardine minced meat model system, the squid protein hydrolysate prepared by Papain has similar lipid oxidation inhibition ability as ascorbic acid [247]. Zein hydrolysate has been proven to effectively inhibit lipid oxidation, reduce the production of hydrogen peroxide and TBARS, and significantly improve the oxidative stability of model oils [248].…”
Section: Functional Ingredients To Stabilize Food Qualitymentioning
confidence: 99%
“…Nevertheless, some work has been done using protein hydrolysates prepared from edible marine invertebrates. Squid protein hydrolysate prepared using papain was shown to retard lipid oxidation in a sardine mince model system as effectively as ascorbic acid [ 73 ]. Cuttlefish skin gelatin hydrolysate prepared with alcalase delayed lipid oxidation in cooked turkey meat sausage during storage at 4 °C [ 74 ].…”
Section: Potential Applications In Food Therapy and Cosmeticsmentioning
confidence: 99%
“…To make their application as food antioxidant additives economically feasible, it is crucial that such peptides have considerably higher efficacy than crude protein hydrolysates, thus allowing the peptides to be used at low quantities (0.001%–0.02%) [ 18 ]. Otherwise, the use of crude protein hydrolysates, e.g., those prepared from the squid, cuttlefish skin gelatin and shrimp waste [ 73 , 74 , 75 ], are likely more cost-effective options as food antioxidant additives. Moreover, certain aromatic and hydrophobic amino acids that confer antioxidant activity on peptides may impart bitterness.…”
Section: Potential Applications In Food Therapy and Cosmeticsmentioning
confidence: 99%
“…The results showed that a high proportion of the total variance was explained by the quadratic regression model ( R 2 of 0.982), indicating that the model is suitable for the optimization of the extraction parameters [ 23 ]. The R 2 Adj of 0.964 was relatively close to the R 2 Pred of 0.902, corroborating that the model is significant [ 14 ].…”
Section: Resultsmentioning
confidence: 99%